Perfectionism and negative attributional style in underachieving university students - Jokić-Begić, Nataša (2002)
Perfectionism has been defined as the tendency to set execessively high standards and to angage in overly critical self-evaluations (Kawamura, Hunt, Frost & Marten, 2001). On other hand, holding a negattive attributional style has belived to place individuals at greater risk for psychological morbidity than for those who did not make such attributions. High personal standards lead to consistent failure. The impact of failure should be significantly greater for individuals who blame themselves for these failures (Flett et al., 1998). The aim of this study was to exam the association between dimensions of perfectionism, attributional style and perception of academic success in the sample of underachieving university students. The data are collected among university students from different faculties and from different school years on University of Zagreb, Croatia. The results will help in further understanding university students&#8217 ; academic underachievement.